(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The role of lullabies which are an eternal and forever part of folklore in bringing up child according to moral ethical, spiritual and aesthetical principlec will now be discussed in this article that is aimed to bring up young generation as suitable people for our country.